Integrating technology into English language teaching at Indonesian high schools: Teachers reflections - Choiril Anwar; Hartono Hartono; Fatih Yavuz (Universitas Syiah Kuala, 2025)
English Language Teaching (ELT) is something that has changed dramatically in recent times due to technology. Even though it could potentially reshape ELT, appropriate implementation remains a challengefor most teachers who are often uncertain as to how to use technology to improve learning. This article looks into the experiences and reflections of Indonesian high school English teachersintegrating technology into their ELT pedagogical practices, from making lesson plans, having classroom activities, to setting up the assessment. Quantitative and qualitativedata were collected and analyzed through a mixed-methods approach. It involved an online survey distributed to 20 diverse Indonesian high school English teachers as well as semi-structured interviews conducted with 10 teachers. The results indicated that there is an increasing use of technology for ELT purposes, particularly to facilitate language reception,language production, and interaction. Theresults also found some challenges and limitations, including technical issues, training and support, and access equity. These insights can help guidethe future development of Indonesian high school ELT practices, inform investment in technology infrastructure, and support targeted professional development initiatives focused on technology integration. The findings are discussed in the context of existing research on ELT and technology integration, with particular emphasis on their significance for high school English teachers in Indonesia. The results provide implications for ELT policymakers, practitioners, and researchers in Indonesia and evidence the importance of context-sensitive solutions to provide meaningful integration of technology in the variability of Indonesian high school settings.